Prognosis prediction using significant pathological response following neoadjuvant immunotherapy in resectable non-small-cell lung tumors: a meta-analysis - Nie, Fang; Wang, Ying; Shi, Wanting; Zhu, Liru; Hao, Jing; Tao, Rancen (Frontiers in Surgery, 2024)
BackgroundA meta-analysis study was done to figure out how to predict the prognosis of people with resectable non-small-cell lung cancer (NSCLC) who had a significant pathological response following neoadjuvant immunotherapy.MethodsUp until August 2024, a comprehensive literature study was completed, and 2,386 connected studies were revised. The 35 selected studies included 3,118 resectable non-small-cell lung tumor participants at the beginning of the study. Using dichotomous techniques and a fixed or random model, the odds ratio (OR) and 95% confidence intervals (CIs) were used to assess the prediction using significant pathological response following neoadjuvant immunotherapy in resectable NSCLC.ResultsIndividuals with resectable NSCLC had significantly higher major pathological response when comparing neoadjuvant chemo-immunotherapy to neoadjuvant chemotherapy (OR, 5.07; 95% CI, 4.09–6.27, p < 0.001), objective response rate to non-objective response rate (OR, 7.02; 95% CI, 4.28–11.50, p < 0.001), and programmed death-ligand 1 ≥1% to programmed death-ligand ≤1% (OR, 2.49; 95% CI, 1.44–4.30, p = 0.001). However, no significant difference was found in major pathological response between stage III and stage I-II (OR, 1.43; 95% CI, 0.88–2.33, p = 0.15), and squamous cell cancer and non-squamous cell cancer (OR, 1.35; 95% CI, 0.95–1.92, p = 0.09) in individuals with resectable NSCLCs.ConclusionIndividuals with resectable NSCLCs had significantly higher major pathological response when comparing neoadjuvant chemo-immunotherapy to neoadjuvant chemotherapy, objective response rate to non-objective response rate, and programmed death-ligand 1≥1% to programmed death-ligand 1 ≤1%, however, no significant difference was found between stage III and stage I-II, and squamous cell cancer and non-squamous cell cancer. To validate this discovery, more research is required since most of the selected studies had a low sample size, and caution must be implemented when interacting with its values.